The Influence of Halal Labeling and Product Quality on Purchasing Decisions at Otaku Coffee (Study: Customers at Otaku Coffee in Brass District) - Ghiffarant Akmal Rambalie; Heri Prasetyo (Universitas KH. Abdul Chalim Mojokerto, 2026)
The global halal economy sector is experiencing rapid growth with market capitalization reaching US2.4 trillion by 2022, with 60% of halal product purchases made by non-Muslim consumers who consider halal certification as an indicator of superior quality. In Indonesia, the transformation of Muslim consumer behavior shows that the halal label is no longer the sole factor in purchasing decisions, but rather combined with product quality considerations, especially in the more selective millennial and Z generations. This study aims to analyze the influence of halal labeling and product quality on purchasing decisions at Otaku Coffee, a Japanese popular culture-themed cafe business that has never been studied before in the context of a combination of religious identity and foreign pop culture preferences. The benefits of this research are to provide a new understanding of consumer behavior in the international culture-themed food and beverage industry and to fill the void in the literature regarding the unique dynamics between halal and quality aspects in a Japanese cultural cafe business setting. The research method uses a quantitative approach with an analytical descriptive design through multiple regression analysis techniques. The research population is all consumers who buy food and beverage products at Otaku Coffee Kuningan Regency, with purposive sampling technique and a sample size of 100 respondents determined using the Lameshow formula with a confidence level of 95% and a margin of error of 10%. The results showed that the halal label (X1) and product quality (X2) partially and simultaneously had a significant positive effect on purchasing decisions (Y) with a calculated F value of 187.024 and a significance of 0.000 <0.05, and a coefficient of determination (Adjusted R Square of 0.794 or 79.4%, confirming that the two independent variables were able to explain the variation in purchasing decisions very well.